Genome-Wide Association Study Identifies Genetic Risk Factors for Spastic Cerebral Palsy. Issue 3 (7th June 2021) - Hale, Andrew T; Akinnusotu, Oluwatoyin; He, Jing; Wang, Janey; Hibshman, Natalie; Shannon, Chevis N; Naftel, Robert P
Abstract: BACKGROUND: Although many clinical risk factors of spastic cerebral palsy (CP) have been identified, the genetic basis of spastic CP is largely unknown. Here, using whole-genome genetic information linked to a deidentified electronic health record (BioVU) with replication in the UK Biobank and FinnGen, we perform the first genome-wide association study (GWAS) for spastic CP. OBJECTIVE: To define the genetic basis of spastic CP. METHODS: Whole-genome data were obtained using the multi-ethnic genotyping array (MEGA) genotyping array capturing single-nucleotide polymorphisms (SNPs), minor allele frequency (MAF) > 0.01, and imputation quality score (r 2 ) > 0.3, imputed based on the 1000 genomes phase 3 reference panel. Threshold for genome-wide significance was defined after Bonferroni correction for the total number of SNPs tested ( P < 5.0 × 10 –8 ). Replication analysis (defined as P < .05) was performed in the UK Biobank and FinnGen. RESULTS: We identify 1 SNP (rs78686911) reaching genome-wide significance with spastic CP. Expression quantitative trait loci (eQTL) analysis suggests that rs78686911 decreases expression of GRIK4, a gene that encodes a high-affinity kainate glutamatergic receptor of largely unknown function. Replication analysis in the UK Biobank and FinnGen reveals additional SNPs in the GRIK4 loci associated with CP. CONCLUSION: To our knowledge, we perform the first GWAS of spastic CP. Our study indicates that genetic variation contributes to CP risk.